“TOP SPEAK” TO IMPROVE SPEAKING SKILL IN SMP N 3 DOLOPO - Samsul Arifin; Erike Septiani; Yuyun Indarwati; Nisa Nur Hidayah (English Teaching Journal : A Journal of English Literature, Language and Education, 2015)
One of the English skills that has to be learned by the students is speaking. Speaking every day at school will make the students have an ability to speak in public, to deliver their inspirations or views in correct way. Developing this ability can be done by guiding the students to speak English in right way. English is a need in this global and developing world. It can be easier if studying English using media. One of media that can be used is “Top Speak”. This study is aimed to give solution to the junior high school students to develop their ability in speaking English in right way and guide them how to be a public speaker. By doing this research, hopefully the students of junior high school can speak and express their point of views accurately. This research uses legend as the topic for teaching and learning process. The legend is taken from the story in Indonesia that can be learn and known by the students to improve their knowledge. The story is in the form of conversation and the students have to practice the story so they will feel the situation in the story. The researcher uses “Top Speak” to help the students as the property in practicing the story. This practice will make the student easily speak English. The type of this research is descriptive qualitative with the students of SMP N 3 Dolopo as the subject. The researcher uses interview, documentation, field note, and checklist as data collection method. The result of this research shows that the students are very interested in speaking English. It can be seen from the way the students speak in front of the class bravely. Moreover, the media is very interesting for the students. The teacher also can make this media easily. This study found some problems during the research such as the location of the school, the schedule of the research, time allotment for the process of making the media, and the students’ shyness to speak in public area.